Comprehensive Evaluation of Safety Emergency Plans for Petrochemical Enterprises under Interval Valued Trapezoidal Neutrosophic Set to Enhance Preparedness and Risk Mitigation - Hailing Chen (Neutrosophic Sets and Systems)
Safety production incidents have had a significant impact on people's livelihoods and property as the petrochemical industry has grown. To prevent and respond to various types of mishaps, numerous nations have created emergency response systems. This study proposes a decision-making approach for evaluation of safety emergency plans for petrochemical enterprises under the uncertainty framework. We use the neutrosophic sets to deal with the uncertainty and vague information. This study uses the interval valued trapezoidal neutrosophic set (IVTNS). We define a set of definition related to IVTNS and their operations. Two decision making methods are used in this study such as LBWA to compute the criteria weights and CoCoSo method to rank the alternatives. This study uses nine criteria and eleven alternatives to be evaluated in the decision-making problem. The sensitivity analysis shows the ranks of the alternatives are stable under different cases.